‘Primarily, I want to be an instrument of change’: Nana Mahomo’s Contribution to the Anti-Apartheid Struggle (Historia, 2025)
As democratic South Africa continues to reflect on its apartheid past, the number of political biographies about individuals who shaped this historical period is growing, especially about those who fought against apartheid. Much of this work is focused on men and women whose contributions can be linked to a particular resistance movement and whose legacies are free from significant controversy. Yet, there are many anti-apartheid activists whose narratives fit awkwardly into democratic South Africa’s new-nationalist history or the official histories of specific liberation movements. One individual who falls into the latter category is Nana Mahomo. Up to now, Mahomo’s contribution to the anti-apartheid struggle in the historiography has been tangential and fragmented. This article constructs a comprehensive overview of Mahomo’s anti-apartheid work and explores how exile shaped the development of his political activism. His story illustrates how access to support networks defined the political trajectories of individuals in exile and how such trajectories interacted with peoples’ own political convictions. This was especially true for activists like Mahomo, much of whose anti-apartheid work was not tied to a South African liberation movement. Finally, the controversial nature of some of Mahomo’s anti-apartheid work strengthens our historiographical understanding of the struggle against apartheid by moving beyond a two-dimensional narrative of heroes versus sellouts.
Keywords: Nana Mahomo; political biography; biography; liberation history; anti-apartheid; Pan Africanist Congress; American Federation of Labor and Congress of Industrial Organizations